The Enhancement of Regional Disaster Management Agencies (BPBD) of Sumbawa Regency’s Capability in Flash Flood Management Through Aid Assistance of Japan International Cooperation Agency (JICA) - Nudia Vebina Ayumahani; Dina Ruslanjari (Indonesian Association for Public Administration, 2018)
The need for enhancing capability has a very important significance in effective disaster management activities. Regional Disaster Management Agencies (BPBD) of Sumbawa Regency established cooperation with the Japan International Cooperation Agency (JICA) in enhancing the capability of flash flood management. The purpose of this research was to review and evaluate the JICA’s aid assistance programs toward BPBD of Sumbawa Regency, hereafter analyze the impact of the programs. Evaluation and analysis of this research were measured by three indicators of capability which is resources, leadership and policy implementation. This research used a qualitative descriptive method and proceed through the source and method triangulation. The researcher used purposive sampling technique in choosing seven informants from BPBD of Sumbawa Regency’s staff. The results showed that JICA’s aid assistance programs towards BPBD of Sumbawa Regency had been achieved by the targets and goals that have been determined. This program has impacted on enhancing the capability of resources that leads to the ability in Mapping, Technical Guidelines (JUKNIS) and Disaster Management Plan (RPB). Increasing the capability of Human Resources (HR) gives the effect of increasing capability in other fields such as financial resource capability, technical resource capability, leadership capability and policy implementation capability. The main factors in the success of the capability enhancement are the discipline factor of BPBD staff, high willingness to improve capability by BPBD staff, capability- enhancing programs, and clear direction from JICA.